2017
DOI: 10.3389/fnhum.2017.00311
|View full text |Cite|
|
Sign up to set email alerts
|

Temporality of Features in Near-Death Experience Narratives

Abstract: Background: After an occurrence of a Near-Death Experience (NDE), Near-Death Experiencers (NDErs) usually report extremely rich and detailed narratives. Phenomenologically, a NDE can be described as a set of distinguishable features. Some authors have proposed regular patterns of NDEs, however, the actual temporality sequence of NDE core features remains a little explored area.Objectives: The aim of the present study was to investigate the frequency distribution of these features (globally and according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 32 publications
(65 reference statements)
6
29
3
Order By: Relevance
“…We found a prevalence of 10% using the same criteria in our previous crowdsourcing online survey on NDE and REM intrusion (Kondziella, Dreier & Olsen, 2019), indicating that this prevalence is quite robust. Unlike most previous reports in which NDE were almost always associated with peace and well-being (Thonnard et al, 2013; Charland-Verville et al, 2015; Martial et al, 2017, 2018; Cassol et al, 2018), we confirmed our earlier findings that many people find their NDE unpleasant (Kondziella, Dreier & Olsen, 2019). However, experiences with the cut-off score of ≥7 GNDES points were reported significantly more often as pleasant (49%) than experiences with a lower score (13%).…”
Section: Discussionsupporting
confidence: 89%
“…We found a prevalence of 10% using the same criteria in our previous crowdsourcing online survey on NDE and REM intrusion (Kondziella, Dreier & Olsen, 2019), indicating that this prevalence is quite robust. Unlike most previous reports in which NDE were almost always associated with peace and well-being (Thonnard et al, 2013; Charland-Verville et al, 2015; Martial et al, 2017, 2018; Cassol et al, 2018), we confirmed our earlier findings that many people find their NDE unpleasant (Kondziella, Dreier & Olsen, 2019). However, experiences with the cut-off score of ≥7 GNDES points were reported significantly more often as pleasant (49%) than experiences with a lower score (13%).…”
Section: Discussionsupporting
confidence: 89%
“…Items that did not survive multiple comparison correction (experiences of extrasensory perception, life-review, precognition of future events, increased speed of thoughts and seeing deceased people/relatives) are also items that are less commonly endorsed in ‘actual’ NDEs (Schwaninger et al, 2002; Greyson, 2003; Vanhaudenhuyse et al, 2009). The Affective subscale of the NDE scale was scored particularly highly under DMT, and emotion is also a prominent feature of actual NDEs (Greyson, 1983, 2003; Schwaninger et al, 2002; Martial et al, 2017). Subtle differences that were apparent between the DMT condition and NDEs (e.g., the experience of entering an unearthly realm was enhanced for DMT vs. actual NDEs, whereas coming to a point of no return was scored higher in actual NDEs compared with the DMT experience) may be explainable by the very different contexts in which these experiences occur (e.g., DMT was given here with prior screening, psychological preparation and consent in a safe laboratory setting vs. an NDE occuring during an illness or unexpected accident) as much as differences due to the inducers themselves or their associated neurobiologies.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the temporal sequence of events unfolding during an NDE is highly variable between people and no prototypical sequence was identifiable in a sample of 154 participants, although four main dimensions were relatively consistent, namely: ‘out-of-body experiences,’ ‘seeing a bright light,’ ‘encountering spirits/people,’ and a ‘feeling of peace’ (Martial et al, 2017). The potential heterogeneity of NDEs cautions us to consider how intra and inter-individual variables, cultural characteristics and the environmental and psychological context in which they take place may influence the content of experiences as well as whether and how they are reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations